A Novel Cytotoxic Steroidal Saponin from the Roots of Asparagus cochinchinensis - Ji-Young Kim; He Yun Choi; Hye Mi Kim; Jung-Hye Choi; Dae Sik Jang (Plants, 2021)
A new steroidal saponin, 26-O-β-d-glucopyranosyl-(25R)-furost-5-ene-3β,22α,26-triol 3-O-(1−4)-β-d-glucopyranosyl-α-l-rhamnopyranosyl-(1−2)-[α-l-rhamnopyranosyl-(1−4)]-β-d-glucopyranoside [asparacochioside A (1)] was isolated from a hot water extract of the roots of Asparagus cochinchinensis, together with the known steroidal saponins protodioscin (2), methyl protodioscin (3), aspacochioside A (4), aspacochioside C (5), 15−hydroxypseudoprotodioscin (6), and chamaedroside E (7). The structure of the new compound 1 was determined by interpretation of its spectroscopic data (1D- and 2D-NMR and HR−Q−TOF−MS) and sugar analysis. The isolated compounds 1−7 were tested for their in vitro cytotoxicity against human ovarian cancer cell lines (A2780 and SKOV3). Asparacochioside A (1) exhibited a significant cytotoxicity against both A2780 and SKOV3 cells with IC50 values of 5.25 ± 2.2 and 46.82 ± 9.43 μM, respectively. Furthermore, asparacochioside A (1) significantly increased the percentage of Annexin V-positive cells (apoptotic cells), suggesting that asparacochioside A induces ovarian cancer cell death via apoptosis.